Penerapan Corporate Social Responsibility (CSR) pada PT. Nampar Nos Kabupaten Manggarai - Maria Minarti Nandi; Minarni A. Dethan; Maria P. L. Muga (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The purpose of this study is to analyze the Implementation of Corporate Social Responsibility (CSR) at PT Nampar Nos Ruteng. The research method used in this study is descriptive qualitative which aims to understand the phenomenon in depth regarding how the implementation of Corporate Social Responsibility can help PT Nampar Nos in managing the environmental impact of its operational activities. Through data collection focusing on direct observation, interviews, or document analysis. The results of the study that Corporate Social Responsibility (CSR) at PT. Nampar Nos has been implemented optimally. The results of the study indicate that PT Nampar Nos balances economic benefits and environmental sustainability through reforestation programs, empowerment of local workers, and management of plastic waste by UMKM.